The Moral Economy of Finance: Reframing Profit Through the Lens of Social Justice and Collective Well-Being - Setiady, Jasmine (Sahabat Publikasi, 2025)
The modern financial paradigm generally prioritizes profit as its main objective, often neglecting moral and social justice aspects. This condition creates inequality and reduces the role of finance as a means for collective welfare. This study aims to reframe the understanding of profit through a moral economy perspective, emphasizing the values of social justice and collective welfare. The research method used is qualitative, through in-depth interviews with business actors and analysis of related documents. The results of the study emphasize that profit is no longer understood solely in materialistic terms, but is also related to moral and ethical values. Business actors place profit as a means of achieving social good, which provides inner satisfaction beyond financial value. Profit is perceived as an indicator of success in creating a fair and beneficial social impact on society. However, there are challenges in the form of moral conflicts between maximizing short-term profits and maintaining the principles of social justice. The implications of this research confirm that the application of moral economics in finance can be the foundation for building a more inclusive and sustainable business and financial system that supports collective welfare.